PENYALAHGUNAAN DANA DEPOSITO MILIK NASABAH DITINJAU DARI KETENTUAN HUKUM PERBANKAN SYARIAH - Salma Fauziah; Lastuti Abubakar; Tri Handayani (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2022)
AbstractIslamic banks in carrying out their business activities are very likely to be faced with a dispute involving customers and the Islamic bank itself. Not infrequently these disputes arise due to the actions of employees of Islamic banks. This study aims to examine the competence in sharia banking dispute resolution and legal considerations in the Supreme Court Decision No. 2454k/pdt/2019 is related to the legal provisions of Islamic banking. This study uses a qualitative method with a normative juridical approach as well as a descriptive analytical research specification. The results of the study indicate that the absolute competence of sharia banking dispute resolution only exists in the Religious Courts. In addition, BRI Syariah Bank's liability for compensation to customers is a form of taking over the responsibilities of employees by the bank as regulated in Article 1367 of the Civil Code. The compensation is based on the principle of prudence, risk management of Islamic banks, and the bank's function as an agent of trust.Keywords: Islamic Bank, Competence, Responsibility